Pengabdian Masyarakat BKM UCIC dengan Panti Asuhan Siti Khadijah Al-Zahroh Melalui Kegiatan Lomba Kreatifitas Anak - Amroni; Dewi Laily Purnamasari; Sudadi Pranata; Marsani Asfi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service was carried out at the Siti Khadijah Orphanage as part of a routine program for the Catur Insan Cendekia University academic community in 2021. This activity was coordinated by the Student Coordination Board (BKM) of the Catur Insan Cendekia University (UCIC). The activities held in the form of an internal competition, namely drawing and coloring between the children of the orphanage as well as giving donations for the orphanage. The theme of the activity is UCIC Sharing in Creativity in Reaching the Future. The implementation of PKM begins with planning activities, seeking sponsorship of activities, implementing competitions and giving donations as well as evaluating the results of activities. The activity planning comes from the BKM routine work program and is part of the PKM activities at the Catur Insan Cendekia University. The sponsorship of this activity was personally initiated by the entire UCIC academic community from lecturers, education staff and students. The purpose of the implementation is to foster caring attitudes among others during the pandemic, as well as to build joy and creativity for children in orphanages. It is hoped that the spirit of social solidarity will grow for the UCIC academic community and contribute to the community, especially in the city of Cirebon.